Performance Appraisal in Indonesian Local Government - Wigunawan, Hendriarto; Noor, Irwan; Haris Wanto, Alfi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
In 2014 Indonesian government enacted a hybrid performance appraisal system that evaluates both civil servants’ behaviors and annual targets (SKP). Under qualitative method, the paper tries to examine the practice of this new performance appraisal system by observing the case of Banyumas Regency. Data are collected from interviewing personnel in Banyumas Civil Service Agency (BKD Banyumas) and official documents. This paper focuses on the strategies used by the government to implement the system and the constraining factors of the implementation. The finding shows that the appraisal system emerges problems such as inflexible individual targets, complexity of procedures, bias and less reliable results, and lack of appreciation for performers. Therefore it can be concluded that the system has many weaknessess that lead an unfair and unreliable evaluation.